2001
DOI: 10.1136/thorax.56.9.696
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced survival of lung granulocytes in an animal model of asthma: evidence for a role of GM-CSF activated STAT5 signalling pathway

Abstract: Background-As granulocyte/macrophage colony stimulating factor (GM-CSF) mediated delay of granulocyte apoptosis contributes to the accumulation of inflammatory cells at the site of inflammation in many diseases, we sought to determine whether asthma is also associated with a GM-CSF dependent increase in lung granulocyte survival. Moreover, because GM-CSF mediates its eVects through activation of signal transducer and activator of transcription 5 (STAT5), we also investigated the potential role of STAT5 in alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…In a recent study, TURLEJ et al [16] found an increased resistance to apoptosis in alveolar neutrophils from heaves-affected horses; heaves is regarded to be an animal model for COPD or asthma [10]. The authors could not detect a significant difference in resistance to apoptosis of peripheral blood neutrophils.…”
Section: Discussionmentioning
confidence: 73%
“…In a recent study, TURLEJ et al [16] found an increased resistance to apoptosis in alveolar neutrophils from heaves-affected horses; heaves is regarded to be an animal model for COPD or asthma [10]. The authors could not detect a significant difference in resistance to apoptosis of peripheral blood neutrophils.…”
Section: Discussionmentioning
confidence: 73%
“…Delayed apoptosis of activated granulocytes has been reported to occur in a number of inflammatory conditions in humans or animal models, 5,52 including rheumatoid arthritis, 53 acute pancreatitis, 54 bacterial pneumonia, 55 inflammatory bowel disease, 56 asthma, [57][58][59] and following surgery. 60,61 Failure of these cells to undergo programmed cell death and to be cleared by phagocytes allows persistent and inappropriate inflammation to occur, as activated granulocytes release a number of proinflammatory mediators, which may contribute significantly to the aetiology of the disease.…”
Section: In Vivo Effects Of No and Its Therapeutic Potentialmentioning
confidence: 99%
“…The late-phase response comprises airway obstruction, airway inflammation, and airway hyperreactivity. RAO has been suggested to be the most similar naturally occurring disease in animals to human asthma (35) and has been used as model of human asthma (2,6,17,39).…”
mentioning
confidence: 99%